Learning Evaluation Management: Improving The Quality of Graduates in State Islamic Institute of Palopo - Sabri JH; Baderiah Baderiah (International Journal of Asian Education, 2020)
The purpose of this study was to determine the implementation of learning evaluation management in improving the quality of graduates at the Palopo State Islamic Institute. This type of research is descriptive qualitative, with pedagogical, juridical, and sociological approaches. The objects in the study were academic implementers and students, and the instruments used were observation guidelines, interview guidelines, and documentation. The results showed that the learning evaluation management at IAIN Palopo consisted of planning, organizing, implementing, and evaluating programs. At the planning stage, the academic side prepares every need for learning evaluation, then holds the schedule by referring to the academic calendar and arranges the place for lectures, at the evaluation stage, the UTS and UAS are supervised by a lecturer or lecturer who teaches the subject in question. Constraints in learning evaluation management include; the incomplete several course material so that it affects planning; besides that, some students who have not received a score in the previous semester (comprehensive examination), in the organizational aspect, some lecturers are late in entering exam questions. Some have even tested the material but did not provide information to the study program/faculty, aspects of the facilities that have less influence on organizing learning evaluation. Obstacles in the implementation of the evaluation are the lack of student preparation in facing exams, the existence of cheating by students during the exam, and the constraints on program evaluation, namely the absence of a set time in evaluating the program.